Implementation of Differentiated Learning in the Merdeka Belajar Curriculum for Elementary Schools - Aziz, Mursal; Napitupulu, Dedi Sahputra; Tanjung, Siti Aminah (Journal of Elementary Educational Research, 2024)
This study explores the implementation of differentiated learning in the Merdeka Curriculum at the Integrated Islamic Elementary School in Kampung Pajak, North Labuhanbatu, aiming to tailor the learning process to the unique needs and characteristics of students. Using a qualitative method with a descriptive approach, the research involved interviews, observations, and documentation from teachers, the principal, and third-grade students. The findings indicate that differentiated learning at this school is implemented through several key aspects: 1) creating a comfortable and supportive learning environment, 2) conducting continuous assessment to gauge student readiness, 3) teacher responsiveness in understanding students' needs and characteristics, and 4) effective classroom management. While this approach successfully enhances student motivation and academic outcomes, some challenges were encountered, including limited preparation time and varying student abilities. This study also compares its findings with previous research, showing that differentiated learning, when supported by an adequate environment and assessment, can increase active participation and student achievement. The implications of this research provide educators with insights into strategies to optimize differentiated learning, especially in elementary schools with limited resources under the Merdeka Curriculum.